Kinin B1 Receptor in Adipocytes Regulates Glucose Tolerance and Predisposition to Obesity - Mori, Marcelo A.; Sales, Vicência Micheline; Motta, Fabiana Louise; Fonseca, Raphael Gomes; Alenina, Natalia; Guadagnini, Dioze; Schadock, Ines; Silva, Elton Dias; Torres, Hugo A. M.; dos Santos, Edson Lucas; Castro, Charlles Heldan; D’Almeida, Vânia; et al. (PLOS ONE, 2012)
Background Kinins participate in the pathophysiology of obesity and type 2 diabetes by mechanisms which are not fully understood. Kinin B1 receptor knockout mice (B1−/−) are leaner and exhibit improved insulin sensitivity. Methodology/Principal Findings Here we show that kinin B1 receptors in adipocytes play a role in controlling whole body insulin action and glucose homeostasis. Adipocytes isolated from mouse white adipose tissue (WAT) constitutively express kinin B1 receptors. In these cells, treatment with the B1 receptor agonist des-Arg9-bradykinin improved insulin signaling, GLUT4 translocation, and glucose uptake. Adipocytes from B1−/− mice showed reduced GLUT4 expression and impaired glucose uptake at both basal and insulin-stimulated states. To investigate the consequences of these phenomena to whole body metabolism, we generated mice where the expression of the kinin B1 receptor was limited to cells of the adipose tissue (aP2-B1/B1−/−). Similarly to B1−/− mice, aP2-B1/B1−/− mice were leaner than wild type controls. However, exclusive expression of the kinin B1 receptor in adipose tissue completely rescued the improved systemic insulin sensitivity phenotype of B1−/− mice. Adipose tissue gene expression analysis also revealed that genes involved in insulin signaling were significantly affected by the presence of the kinin B1 receptor in adipose tissue. In agreement, GLUT4 expression and glucose uptake were increased in fat tissue of aP2-B1/B1−/− when compared to B1−/− mice. When subjected to high fat diet, aP2-B1/B1−/− mice gained more weight than B1−/− littermates, becoming as obese as the wild types. Conclusions/Significance Thus, kinin B1 receptor participates in the modulation of insulin action in adipocytes, contributing to systemic insulin sensitivity and predisposition to obesity.